Biology and culture of sea bass (Lates calcarifer Bloch) - Kungvankij, P.; Pudadera, B.J., Jr; Tiro, L.B., Jr; Potestas, I.O (Network of Aquaculture Centres in Asia, 1986)
NACA training manual series ; no. 3Aquaculture extension manual / SEAFDEC Aquaculture Department ; no. 11